2009
DOI: 10.1123/jis.2.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Consequences of Athletic Burnout among College Athletes

Abstract: It has been shown that it takes 10 years or 10,000 hours of deliberate practice to develop one's talent in any field, including athletics (Ericsson, 1996). Given the amount of time, sacrifice, and effort needed to become an expert athlete, it is not surprising that researchers have been interested in examining burnout in competitive athletes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 29 publications
(64 reference statements)
0
59
0
2
Order By: Relevance
“…First, the current sample was delimited to collegiate swimming/diving and track/field athletes. The collegiate sport environment is well suited for the study of burnout and well-being (Gould & Whitley, 2009). Nonetheless, the examination of athletes across a range of career stages and competitive levels would offer needed developmentally informed understanding of athlete burnout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the current sample was delimited to collegiate swimming/diving and track/field athletes. The collegiate sport environment is well suited for the study of burnout and well-being (Gould & Whitley, 2009). Nonetheless, the examination of athletes across a range of career stages and competitive levels would offer needed developmentally informed understanding of athlete burnout.…”
Section: Discussionmentioning
confidence: 99%
“…College teams were chosen because understanding of burnout in this performance environment has been described as important for promotion of athlete health and safety (Gould & Whitley, 2009). Descriptive information is based on participants (N = 429) who completed demographic questions administered at Wave 1.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Further research by Kentta and colleagues (Kentta & Hassmaen, 1998;Kentta, Hassmen & Raglin, 2001) has shown that physical training is a component in the burnout process. However, burnout is not just a matter of physical overtraining (Gould & Whitley, 2009). The burnout process contains psychological and social components and to only assume training as a causal factor would leave an incomplete picture.…”
Section: Theoretical Models Of Burnoutmentioning
confidence: 99%
“…In preparing a player, self-regulation becomes centrally important because the drive to succeed and an inability to cope with the demand can cause stress and reduce well-being (Gould & Whitley, 2009). In addition, reduced self-regulation can eventually result in burnout (Goodger & Jones, 2012).…”
Section: Introductionmentioning
confidence: 99%